Development of maraviroc, a CCR5 antagonist for treatment of HIV, using a novel tropism assay. (11th May 2015) - van der Ryst, Elna; Heera, Jayvant; Demarest, James; Knirsch, Charles
Abstract : Assays to identify infectious organisms are critical for diagnosis and enabling the development of therapeutic agents. The demonstration that individuals with a 32‐bp deletion within the CCR5 locus were resistant to human immunodeficiency virus (HIV) infection, while those heterozygous for the mutation progressed more slowly, led to the discovery of maraviroc (MVC), a CCR5 antagonist. As MVC is only active against CCR5‐tropic strains of HIV, it was critical to develop a diagnostic assay to identify appropriate patients. Trofile™, a novel phenotypic tropism assay, was used to identify patients with CCR5‐tropic virus for the MVC development program. Results of these clinical studies demonstrated that the assay correctly identified patients likely to respond to MVC. Over time, the performance characteristics of the phenotypic assay were enhanced, necessitating retesting of study samples. Genotypic tropism tests that have the potential to allow for local use and more rapid turnaround times are also being developed.